Optical fiber mercury biosensor based on immobilized urease and bromothymol blue onto the alginate-chitosan membrane in the flow-system - Hermanto, Dhony; Mudasir, Mudasir; Siswanta, Dwi; Kuswandi, Bambang; Ismillayli, Nurul (Kuwait Journal of Science, 2022)
An optical fiber biosensor has been developed for the detection of mercury ion based on inhibition of urease immobilized onto alginate–chitosan membrane, coupled with bromothymol blue (BTB) in the flow system. To get a good performance of the biosensor toward Hg(II) ion detection, the experimental parameters of the biosensor were optimized. Here, the maximum wavelength was detected at 580 nm, with the optimum response at pH of 6. The calibration curve had a dynamic working range at 10 to 500 μg/L of Hg(II) ion with a detection limit of 12.1 μg/L biosensor has been performed by the addition of 1 mM ethylenediaminetetraacetic acid (EDTA) solution, in which five-time cycles have been achieved with the inhibition decrease to 9.94% from the original biosensor response. Applying the biosensor to the real samples showed conformity of results with the reference method, cold vapor atomic absorption spectrometry (CV-AAS). Therefore, this biosensor can be used as a method for routine analysis in the determination of Hg(II) concentration in an aqueous sample